Nuclear S-Nitrosylation Defines an Optimal Zone for Inducing Pluripotency. Issue 13 (24th September 2019) - Chanda, Palas K.; Meng, Shu; Lee, Jieun; Leung, Honchiu E.; Chen, Kaifu; Cooke, John P.
Abstract : Background: We found that cell-autonomous innate immune signaling causes global changes in the expression of epigenetic modifiers to facilitate nuclear reprogramming to pluripotency. A role of S -nitrosylation by inducible nitric oxide (NO) synthase, an important effector of innate immunity, has been previously described in the transdifferentiation of fibroblasts to endothelial cells. Accordingly, we hypothesized that S -nitrosylation might also have a role in nuclear reprogramming to pluripotency. Methods: We used murine embryonic fibroblasts containing a doxycycline-inducible cassette encoding the Yamanaka factors ( Oct4, Sox2, Klf4, and c- Myc ), and genetic or pharmacological inhibition of inducible NO synthase together with the Tandem Mass Tag approach, chromatin immunoprecipitation-quantitative polymerase chain reaction, site-directed mutagenesis, and micrococcal nuclease assay to determine the role of S -nitrosylation during nuclear reprogramming to pluripotency. Results: We show that an optimal zone of innate immune activation, as defined by maximal yield of induced pluripotent stem cells, is determined by the degree of activation of nuclear factor κ-light-chain-enhancer of activated B cells; NO generation; S -nitrosylation of nuclear proteins; and DNA accessibility as reflected by histone markings and increased mononucleosome generation in a micrococcal nuclease assay. Genetic or pharmacological inhibition of inducible NO synthase reduces DNA accessibility and suppresses induced pluripotent stem cell generation. The effect of NO on DNA accessibility is mediated in part by S -nitrosylation of nuclear proteins, including MTA3 (Metastasis Associated 1 Family Member 3), a subunit of NuRD (Nucleosome Remodeling Deacetylase) complex. S -Nitrosylation of MTA3 is associated with decreased NuRD activity. Overexpression of mutant MTA3, in which the 2 cysteine residues are replaced by alanine residues, impairs the generation of induced pluripotent stem cells. Conclusions: This is the first report showing that DNA accessibility and induced pluripotent stem cell yield depend on the extent of cell-autonomous innate immune activation and NO generation. This "Goldilocks zone" for inflammatory signaling and epigenetic plasticity may have broader implications for cell fate and phenotypic fluidity. Abstract : Supplemental Digital Content is available in the text.